2006
DOI: 10.1073/pnas.0601026103
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as signaling organelles in the vascular endothelium

Abstract: Vascular endothelial cells are highly glycolytic and consume relatively low amounts of oxygen (O2) compared with other cells. We have confirmed that oxidative phosphorylation is not the main source of ATP generation in these cells. We also show that at a low O2 concentration (<1%) endogenous NO plays a key role in preventing the accumulation of the ␣-subunit of hypoxia-inducible factor 1. At higher O2 concentrations (1-3%) NO facilitates the production of mitochondrial reactive oxygen species. This production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
258
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 319 publications
(278 citation statements)
references
References 54 publications
(50 reference statements)
12
258
0
3
Order By: Relevance
“…Using DPI to inhibit ROS production in HUVECs precluded the rise of intracellular ROS levels observed after 48 h and resulted in the complete inhibition of the tube formation. A cell viability assay proved that the cells remain viable during their culture in media containing DPI, suggesting that the inhibition of tubulogenesis is not due to cell death, which agrees with other studies demonstrating the effects of DPI on angiogenesis (34,45). Treatment with DPI was also previously shown to inhibit mitochondrial respiration (28), which may in turn increase the DO levels available in the gel.…”
Section: C437 Oscillations In Dissolved Oxygen During Tubulogenesissupporting
confidence: 75%
See 4 more Smart Citations
“…Using DPI to inhibit ROS production in HUVECs precluded the rise of intracellular ROS levels observed after 48 h and resulted in the complete inhibition of the tube formation. A cell viability assay proved that the cells remain viable during their culture in media containing DPI, suggesting that the inhibition of tubulogenesis is not due to cell death, which agrees with other studies demonstrating the effects of DPI on angiogenesis (34,45). Treatment with DPI was also previously shown to inhibit mitochondrial respiration (28), which may in turn increase the DO levels available in the gel.…”
Section: C437 Oscillations In Dissolved Oxygen During Tubulogenesissupporting
confidence: 75%
“…The direction of the change in ROS production due to changes in DO levels depends on both the cell type and the exposure time to various DO levels. However, the vast majority of the results obtained on ECs agree on the fact that hypoxia (34) and reoxygenation (46,47) increase the levels of intracellular ROS. Previous studies have shown that an optimal level of NOXderived ROS is required for EC proliferation, migration, and capillary formation (2,36).…”
mentioning
confidence: 59%
See 3 more Smart Citations